Curvilinear Effects of Extraversion on Socialization Outcomes Among Chinese College Students - Deng, Yingxin; Chen, Huitian; Yao, Xiang (Frontiers in Psychology, 2021)
The authors examine the too-much-of-a-good-thing effect (TMGT effect) in a model showing that extraversion has a curvilinear relationship with social acceptance and depression. A study of 371 freshmen in a Chinese university showed that extraversion had a curvilinear relationship with social acceptance, such that the relationship was significantly positive from lower to moderate levels of extraversion, but the positive relationship leveled off at higher levels of extraversion. Extraversion also had a curvilinear relationship with depression, such that the relationship was significantly negative from lower to moderate levels of extraversion, but the negative relationship leveled off at higher levels of extraversion. The study indicates that beyond a certain point, the beneficial effects of extraversion on socialization outcomes were diminished. That is, higher levels of extraversion were not associated with more positive socialization outcomes (though they were not associated with worse outcomes either) when extraversion exceeded certain point. Implications of theory and practice, as well as limitations and directions for future research, are discussed.